(untitled) (Al-Aasar, 2026)
This study examines how traditional and alternative assessment methods operate at the university level. It focuses on how these styles affect skill development and learning. Traditional styles include quizzes and short tests. These kinds of tests are quick and easy to use in large classes and give results in less time. This research combines quantitative data on students’ learning outcomes and surveys, while qualitative data were collected through interviews and discussions with higher-education-level students. The main purpose of this research is to compare traditional and alternative methods and examine how they work at the university level. How quizzes, presentations, peer group observations and tests help to develop critical thinking at the university level. This research draws a pragmatic worldview and studies 50 undergraduate students at the university. This study presents alternative practices that enhance student motivation, learning skills, and critical thinking. Research methodology highlights the challenges which are barriers to alternative methods, such as limited resources or poor time management. Discussion concludes with the idea that formative assessment helps develop students’ critical thinking and promotes creativity. In Pakistani universities, where large classes, language barriers, and limited resources are common, the results show that irrationalism styles increase students’ interest and help them improve their weaknesses. Overall, the findings suggest a balanced approach. Combining the challenges of traditional tools with the engagement of crucial styles can produce better results.